Bentuk Penyajian Tari Iyo-iyo Pada Upacara Pengangkatan Gelar Depati Ninik Mamak Di Desa Tanjung Pauh Mudik, Kerinci - Ravena Lutiyasa; Nerosti Nerosti (SENDRATASIK UNP, 2022)
This research aims to find out and describe the Form of Presentation of Iyo-iyo Dance at the depati Ninik Mamak title appointment event in Tanjung Pauh Mudik Village of West Kerinci Lake District, Kerinci Regency. This type of research is qualitative research with descriptive analytical methods. These research instruments are researchers themselves and are assisted by supporting instruments such as stationery, notebooks and cameras. This type of data uses primary data and secondary data. Data collection techniques are carried out by means of library studies, observations, interviews and documentation. The steps of analyzing data are collecting data, describing data and inferring data. The results of this study showed that the form of presentation of Iyo-iyo Dance at the Depati Ninik Mamak Title Ceremony began with a speech from the host, a speech from a ceremony as well as the delivery of hajat, followed by an offering from the butino child, followed by the pick-up of Mangku Depati, customary parno (religious greeting), followed by prayer and Jeddah, and the last performance of Iyo-iyo Dance. Iyo-iyo dance consists of 2 movements, and is only danced by female dancers who have something to do with Depati Ninik mamak, the butino son of Depati Ninik Mamak with a number of dancers of 15-30 people. Iyo-iyo dance uses internal music, which is the music of the dendang derived from the poet's voice, and this dance uses frankincense to spurt dancers who are believed to summon the spirits of ancient ancestors. The function of Iyo-iyo Dance at the Depati Ninik Mamak Title Appointment Ceremony is as entertainment for the people who witnessed it and as a form of respect to Depati who was appointed his title.